1994
DOI: 10.1128/mcb.14.6.4173
|View full text |Cite
|
Sign up to set email alerts
|

Homologous recombination of monkey alpha-satellite repeats in an in vitro simian virus 40 replication system: possible association of recombination with DNA replication.

Abstract: To study homologous recombination between repeated sequences in an in vitro simian virus 40 (SV40) replication system, we constructed a series of substrate DNAs that contain two identical fragments of monkey a-satellite repeats. Together with the SV40-pBR322 composite vector encoding Apr and KMr, the DNAs also contain the Escherichia coli galactokinase gene (galK) positioned between two a-satellite fragments. The a-satellite sequence used consists of multiple units of tandem 172-bp sequences which differ by mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

1995
1995
2008
2008

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 51 publications
1
7
0
Order By: Relevance
“…Therefore, as was observed by others for UV, irradiation during replication should lead to increased levels of chromatid breaks (Kaufmann and Wilson, 1994). Replication-associated recombination serves to bypass unrepaired DNA lesions that inhibit chain elongation, and there are hints that also in SV40 based systems homologous recombination is coupled to DNA replication (Sarasin and Hanawalt, 1978;Kawasaki et al, 1994;Cox et al, 2000). Therefore, we propose that the p53-dependent downregulation of radiation induced recombination is directed towards replication-associated processes.…”
Section: Indications For An Antagonistic Role Of P53 During Replicatisupporting
confidence: 62%
“…Therefore, as was observed by others for UV, irradiation during replication should lead to increased levels of chromatid breaks (Kaufmann and Wilson, 1994). Replication-associated recombination serves to bypass unrepaired DNA lesions that inhibit chain elongation, and there are hints that also in SV40 based systems homologous recombination is coupled to DNA replication (Sarasin and Hanawalt, 1978;Kawasaki et al, 1994;Cox et al, 2000). Therefore, we propose that the p53-dependent downregulation of radiation induced recombination is directed towards replication-associated processes.…”
Section: Indications For An Antagonistic Role Of P53 During Replicatisupporting
confidence: 62%
“…Moreover, the eccDNA patterns detected for different VicTR-A and VicTR-B subfamilies or higher-order repeats suggest that relatively long regions (tens to hundreds of nucleotides) of high sequence similarity are required for efficient recombination. It has been reported that efficiency of homologous recombination depends on similarity of involved sequences [ 34 - 36 ] and is proportional to the length of the similarity [ 37 ]. If the length or degree of sequence similarity is decreased, the rate of recombination is reduced rapidly.…”
Section: Discussionmentioning
confidence: 99%
“…The absence of Top3 in mitosis leads to the accumulation of cells with an undivided nucleus in the neck of an elongated bud (Gangloff et al ., 1994b). The associated cell cycle delay at the G 2 –M transition is consistent with an impediment of chromosome segregation, suggesting that Top3 is involved directly in the separation of replicated chromatids or, alternatively, in the resolution of topological structures resulting from either recombination during replication or collapsed replication forks (Young et al ., 1984; Kawasaki et al ., 1994; Zou and Rothstein, 1997). Because no noticeable difference in the timing of diploid spore formation could be detected when meiotic levels of recombination are abolished, we do not believe it likely that Top3 plays a meiotic‐specific role in the DNA synthesis process.…”
Section: Discussionmentioning
confidence: 99%